Cover Image. (15th May 2021) - Kwak, Yeonsu; Shin, Hyunah; Moon, Seongeun; Lee, Kwanhee; Kirk, Jaewon; Park, Yongha; Jeong, Hyangsoo; Sohn, Hyuntae; Han, Jong Hee; Nam, Suk Woo; Yoon, Chang Won; Kim, Yongmin; et al.
Abstract : The cover image is based on the Research Article Investigation of a hydrogen generator with the heat management module utilizing liquid‐gas organic phase change material by Yeonsu Kwak et al., https://doi.org/10.1002/er.6526 .